2016
DOI: 10.1007/s00432-016-2277-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-183 promotes cell proliferation via regulating programmed cell death 6 in pediatric acute myeloid leukemia

Abstract: Combined serum miR-183 and PDCD6 mRNA may serve as a novel prognostic biomarker for pediatric AML. Interestingly, miR-183 may function as an oncogene and may enhance cell proliferation by targeting PDCD6, implying a potential therapeutic target for this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Other studies have shown that expression of GSK3β can inhibit the expression of miR-183 through the β-Catenin/TCF/LEF-1 pathway in human gastric cancer cells, while β-Catenin/TCF/ LEF-1 binds to the promoter of miR-183 and thereby activates the transcription of miR-183 [8]. While in non-small cell lung cancer, they found that TFAP2C blocked AKAP12-mediated cyclin D1 inhibition by inducing the overexpression of miR-183, which shows that TFAP2C is one of the upstream regulators of miR-183 [9]. In breast cancer, the transcription of miR-183 was regulated by ZEB1 and HSF2, HSF2 can upregulate miR-183 expression [10].…”
Section: Regulation Of Mir-183 Expressionmentioning
confidence: 98%
“…Other studies have shown that expression of GSK3β can inhibit the expression of miR-183 through the β-Catenin/TCF/LEF-1 pathway in human gastric cancer cells, while β-Catenin/TCF/ LEF-1 binds to the promoter of miR-183 and thereby activates the transcription of miR-183 [8]. While in non-small cell lung cancer, they found that TFAP2C blocked AKAP12-mediated cyclin D1 inhibition by inducing the overexpression of miR-183, which shows that TFAP2C is one of the upstream regulators of miR-183 [9]. In breast cancer, the transcription of miR-183 was regulated by ZEB1 and HSF2, HSF2 can upregulate miR-183 expression [10].…”
Section: Regulation Of Mir-183 Expressionmentioning
confidence: 98%
“…Increasing evidence has demonstrated that miRNAs participate in various fundamental biological and pathological processes, such as cell differentiation, proliferation, apoptosis, as well as autophagy, indicating their important regulatory roles during carcinogenesis and chemoresistance [21]. It is well documented that dysregulation of miRNAs contributes to a variety of human disease, including AML [22], [23]. In view of the significance of autophagy in the chemoresistance of tumors and the regulatory role of miRNAs in autophagy, better understanding the role of miRNA-regulated autophagy during chemotherapy in AML might contribute to clarifying its mechanism of chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ke et al showed that miR-192 suppressed the proliferation, cell cycle transition of AML cells by targeting CCNT2 (24). In addition, Wang et al demonstrated that miR-183 enhanced the proliferation of pediatric AML cells by targeting programmed cell death 6 (25). miR-135a has been shown to aberrantly expressed in several cancer, including non-small cell lung cancer (26), thyroid carcinoma (27), glioblastoma (28), pancreatic cancer (29), hepatocellular carcinoma (30) and gastric cancer (31).…”
Section: Discussionmentioning
confidence: 99%